SINTESIS NATRIUM PENTAGAMAVUNONAT DAN UJI STABILITASNYA MENGGUNAKAN SPEKTROFOTOMETER UV-Visible - Ely Setiawan; Trisnowati Trisnowati; Dadan Hermawan (Universitas Jenderal Soedirman, 2006)
A research on the synthesis of sodium pentagamavunonat (Na-PGV-0) and its stability test using UV-Visible spectrophotometer were carried out. The synthesis of Na-PGV-0 carried out by reacting PGV-0 in tetrahydrofuran solvent refluxed with sodium ethoxide in mol comparison (1:2) for two hours. Structure elucidation by spectroscopic methods using UV-Visible, IR, 1H-NMR, 13C-NMR and stability test in water using UV-Visible spectrophotometer. The reaction yields 107,21 % (% w/w) products. A products was soluble in water and methanol. Structure elucidation results indicated that the formed compound where the OH phenolic of pentagamavunon-0 was replaced by sodium ions. Stability test shows that decreasing of sodium